Quality and cost considerations in hyponatraemic patients needing hospitalisation (Swiss Medical Weekly, 2018)
BACKGROUND Hyponatraemia is the most common electrolyte disorder encountered in hospitalised patients and has an impact on outcome and survival. However, the risk factors are not yet sufficiently known. AIMS OF THE STUDY This retrospective analysis was conducted with the primary objective to identify the incidence of hyponatraemia in patients, who need hospitalisation from any medical reason, focusing on the quality of treatment and the risk factors for recurrent or prolonged stay due to hyponatraemia. The secondary objectives were the calculation of costs of hyponatraemia caused by hospital stays in the canton of Basel-Landschaft and the additional extrapolation of these costs for the whole country of Switzerland. METHODS 368 patients with a diagnosis of hyponatraemia admitted to three tertiary care centers in 2011 were included. We analysed the risk factors, causes and manifestations of hyponatraemia and their effects on length of stay and outcome. RESULTS Female gender (62%), advanced age (average 75 ± 12 years) and the use of thiazides (r = 0.69, p = 0.03) represented the main risk factors with negative prognostic value concerning hyponatraemia. Hyponatraemia was never asymptomatic. Seventy-three patients (20%) were diagnosed with hyponatraemia due to SIADH (syndrome of inappropriate antidiuretic hormone secretion). The in-hospital mortality rate was 9%, irrespective of the severity of hyponatraemia, and every fifth patient had persistent neurological deficits on discharge from the hospital. Age (r = 0.65, p = 0.03), female sex (r = 0.49, p =0.12; in combination with age >75years r = 0.58, p = 0.049), resumption of risk medication (r = 0.563, p = 0.02) and persistent hyponatraemia on discharge (r = −0.51, p = 0.04) were associated with higher probability of relapse. Our data, extrapolated for Switzerland, yield uncovered annual costs of 93 million CHF, mostly due to in-hospital treatment longer than that reimbursed by SwissDRG (observed median of 9 days, cost coverage by SwissDRG 5 days for non-SIADH hyponatraemia and 6.5 days for SIADH). CONCLUSIONS As even mild hyponatraemia is associated with an increased risk of morbidity and mortality, it is highly important to recognise it. Initial diagnostic evaluation, treatment based on volume status and thorough follow-up are crucial to avoid relapse. Hyponatraemia, based on the results of this retrospective study, constitutes a considerable medical and economic burden in Switzerland and has a serious impact on the hospital balance sheets.